1998
DOI: 10.1016/s0014-5793(98)01483-5
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain‐sensitive H,K‐ATPase: tissue‐specific expression of the mammalian genes encoding the catalytic α subunit1

Abstract: Human ATP1AL1 and corresponding genes of other mammals encode the catalytic K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…The underlying mechanism remains unexplained. It has been revealed that both gastric and non-gastric type of hydrogen/potassium adenosine triphosphatase (H+/ K+-exchanging ATPase) is present in various tissues including cochlear lateral wall, polymorphonuclear leukocytes, kidney, brain, placenta and colon but its functional role has not been well studied (14,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism remains unexplained. It has been revealed that both gastric and non-gastric type of hydrogen/potassium adenosine triphosphatase (H+/ K+-exchanging ATPase) is present in various tissues including cochlear lateral wall, polymorphonuclear leukocytes, kidney, brain, placenta and colon but its functional role has not been well studied (14,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Given ouabain was used as a specific blocker for Na + -K + -ATPase in these studies, and the location of Na + -K + -ATPase has not been verified immunocytochemically, we should keep in mind that ouabain-inhibitable H + -K + -ATPase α subunit may co-exist [35,36]. H + -K + -ATPase has been found in re-absorptive epithelial tissues, including kidney and gastrointestinal tract [36,37].…”
Section: I-2 Na + -K + -Atpase and Ca 2+ -Atpasementioning
confidence: 99%
“…The fact that transgene expression was detected at low levels in the brain and lung by immunoblot analysis of EGFP expression indicates that the mechanism for silencing of the HK␣ 2 gene in the distal colon may be specific to that tissue. Furthermore, the finding of HK␣ 2 transgene expression in the brain and lung was not surprising, because HK␣2 mRNA expression has been reported in the brain from the mouse and rabbit, and the homologous ATP1AL1 mRNA has been detected in the human brain (21). A role of HK␣ 2 in the brain or lung function has not been established.…”
Section: Discussionmentioning
confidence: 99%